Interfaces of the world: Studies in the evolution of consciousness and culture - Ong, Walter J. (London Cornell University Press, 1977)
Drawing on a wide range of disciplineslinguistics, phenomenological analysis, cultural anthropology, media studies, and intellectual historyWalter J. Ong offers a reasoned and sophisticated view of human consciousness different in many respects from that of structuralism. The essays in Interfaces of the Word are grouped around the dialectically related themes of change or alienation and growth or integration. Among the subjects Ong covers are the origins of speech in mother tongues; the rise and final erosion of nonvernacular learned languages; and the fictionalizing of audiences that is enforced by writing. Other essays treat the idiom of African talking drums, the ways new media interface with the old, and the various connections between specific literary forms and shifts in media that register in the work of Shakespeare and Milton and in movements such as the New Criticism. Ong also discusses the paradoxically nonliterary character of the Bible and the concerted blurring of fiction and actuality that marked much drama and narrative toward the close of the twentieth century.